2015
DOI: 10.1111/1751-2980.12255
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular injection of mitomycin C combined with endoscopic dilation for benign esophageal strictures

Abstract: Intramuscular injection of mitomycin C or dexamethasone may prolong the dysphagia-free period and decrease the frequency of repeat dilations compared with conventional endoscopic dilations in patients with benign esophageal strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…We are not sure about this leak, but it is not possible to exclude it. Previous results support MMC injection, but not with short intervals between sessions [ 11 , 17 19 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We are not sure about this leak, but it is not possible to exclude it. Previous results support MMC injection, but not with short intervals between sessions [ 11 , 17 19 ].…”
Section: Discussionmentioning
confidence: 84%
“…The majority of studies reported topical application of MMC with a variety of application techniques, including cotton pledget, microporous balloon, and spraying technique. However, we found 4 studies with 32 adult patients submitted to MMC injection directly in the stricture after dilation [ 11 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory or recurrent strictures should be defined as an anatomic restriction because of a cicatricial luminal compromise or fibrosis resulting in clinical symptoms of dysphagia in the absence of endoscopic evidence of inflammation [10]. Stratifying patients prone to have strictures refractory to traditional endoscopic therapies may help in earlier selection of patients who should be considered for further endoscopic techniques, such as steroid injections, incisional therapy, stent placement, or surgery [15][16][17][18][19]. Stratifying patients prone to have strictures refractory to traditional endoscopic therapies may help in earlier selection of patients who should be considered for further endoscopic techniques, such as steroid injections, incisional therapy, stent placement, or surgery [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prolong the dysphagia-free period, and to decrease the frequency of repeated dilations compared with conventional endoscopic dilations, intramuscular injections of mitomycin C and steroids were suggested. Mitomycin C is a chemotherapeutic agent derived from some Streptomyces species which reduces scars formation when topically applied to a mucosal lesion, and theoretically should prevents esophageal stenosis in selected cases [ 10 , 11 ]. Nevertheless, there is evidence that triamcinolone and other steroids injection in combination with endoscopic dilation is able to reduce the risk of recurrent dysphagia in refractory benign esophageal strictures of peptic origin, with results coming from small-sized studies with poorly defined population and not concerning caustic ingestion [ 12 ].…”
Section: Discussionmentioning
confidence: 99%